(untitled) (CIPEEX, 2025)
The digital era has profoundly transformed electoral propaganda by combining massive reach with real-time interactivity. However, this speed in the circulation of content enhances the spread of false information and exposes gaps in the legal framework, undermining equal opportunities and trust in the democratic process. This study analyzes the legal limits and regulatory challenges of digital propaganda, with emphasis on the use of social media, the dissemination of fake news, and the role of the Electoral Justice. A review of Brazilian regulations (Law No. 9,504/1997, LGPD, and TSE resolutions), an examination of relevant case law, and the study of emblematic cases (the 2008 U.S. elections and the 2018 Brazilian elections) were carried out, complemented by a critical analysis of policies adopted by digital platforms. The results indicate that social media offers high potential for segmentation and engagement, but also fosters polarization and the misuse of personal data. Furthermore, the spread of fake news harms voters’ decision-making, highlighting the need for faster control mechanisms. In response, the Electoral Justice has intensified real-time monitoring and reinforced the requirement of transparency in paid ads, applying punitive sanctions, although it still depends on technological advancements and corporate cooperation. It is concluded that it is essential to establish a dynamic and integrated regulatory framework, capable of reconciling freedom of expression with the fight against disinformation. To ensure the integrity of elections, it is recommended to strengthen ongoing collaboration among legislators, the judiciary, digital platforms, and civil society.